(untitled) (International Journal of Food and Nutritional Sciences, 2021)
India is well known to world for its most excellent and attractive adventure, wildlife, pilgrimage, business and eco tourism places. In the bustling world of travel and exploration, there exists a special breed of individuals who possess a unique blend of vision, innovation, and business acumen where they called as “Tourism Entrepreneurs”. Entrepreneurs in the tourism industry are trailblazers who succeed in their endeavors, whether they are launching a boutique hotel that offers distinctive travel experiences or creating an eco-tourism company that combines adventure with environmental protection. They can create deals that stand out from the competition since they have a solid understanding of the shifting demands and preferences of visitors. On the other hand, due to certain Poor image creation, lack of promotion, inadequate infrastructure, millennial travelers and other constraints. The result of these constraints challenging the tourism entrepreneurship to compete in the present marketing world. Therefore, the study focused to provide certain modern marketing strategies to enhance tourism entrepreneurship in India.